Acute Toxicity Study and In-vivo Anti-inflammatory Activity of Different Fractions of Curculigo orchioides Gaertn. Rhizome in Albino Wistar Rats: Toxicity of Curculigo orchioides Gaertn. rhizome in rats - Mohammad Asif; Ankush Kumar (Iranian Journal of Pharmaceutical Sciences, 2010)
The effects of hydroalcoholic extract (HE) of Curculigo orchioides Gaertn. rhizome (Hypoxidaceae) and its alkaloidal and non-alkaloidal fractions (AF) and (NAF) were evaluated in carrageenan-induced paw edema experimental models of inflammation. The oral administration of HE, their AF and NAF fractions were used at doses of 100, 300 and 500 mg/kg. The effect produced by the HE, AF and NAF fractions were comparable to that of indomethacin with a dose of 10 mg/kg as the reference drug. The percentage of inhibition of inflammation of all extracts was dose dependent. The crude HE showed 22.45%, 35.62% and 39.03% inhibition; AF showed 31.68%, 36.89% and 41.17% inhibition; and NAF showed 28.34%, 34.49% and 37.43% inhibition of induced hind paw edema in rats at doses of 100 mg/kg, 300 mg/kg and 500 mg/kg, respectively, while indomethacin inhibited 48.66% of the edema. The acute toxicity evaluation showed that all extract were not toxic up to 2000 mg/kg (p.o). The results suggest that the anti-inflammatory effects of the extracts as claimed in folk Indian medicine.